Analysis of Sugar-Free Claimed Beverages and Its Potential CustomersAnalysis of Sugar-Free Claimed Beverages and Its Potential Customers - Sunarisa, J (KnE Social Sciences, 2018)
According to Ministry of Health Republic of Indonesia, obesity and diabetes have increased significantly within 31 provinces in Indonesia. To avoid these two foodrelated diseases, people start to be health conscious and show their interest of healthy eating. As a result, more and more beverages companies participate in the healthy trend and develop many healthier drinks with sugar free label to respond the market. Thus, the study is executed in order to understand sugar free beverages market and understand the effect of sugar free label on packaging toward purchase intention. The research is conducted in the form of online questionnaire and experiment to 149 respondents domiciled in Bandung, Indonesia. The questionnaire data is analyzed using cluster analysis. It shows that there are 4 clusters which have distinctive demographic, psychographic, and behavioral characteristics toward sugar free beverages market. The experiment is analyzed using paired t-test and indicates that sugar free claims on beverages packaging increase peoples willingness to buy. This study is expected to help sugar free beverages industry to target the right customers and apply appropriate strategy according to the potential customers characteristics. Keywords: segmentation, cluster analysis, purchase intention, experimental, sugarfree beverages